2021
DOI: 10.3389/fnmol.2021.619496
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Transmembrane Regions, Cholesterol, and Ganglioside Binding Sites in Amyloid-Forming Proteins Indicate Potential for Amyloid Pore Formation

Abstract: Besides amyloid fibrils, amyloid pores (APs) represent another mechanism of amyloid induced toxicity. Since hypothesis put forward by Arispe and collegues in 1993 that amyloid-beta makes ion-conducting channels and that Alzheimer's disease may be due to the toxic effect of these channels, many studies have confirmed that APs are formed by prefibrillar oligomers of amyloidogenic proteins and are a common source of cytotoxicity. The mechanism of pore formation is still not well-understood and the structure and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 107 publications
(132 reference statements)
0
11
0
Order By: Relevance
“…Amyloid β peptides have been shown to oligomerize into ion-permeable transmembrane pores of varying structure, composition, and permeability. Aβ42 oligomers are known to adopt a β-sheet-rich structure in the presence of membrane lipids and self-organize into transmembrane channels permeable to calcium ions, which can cause cell death (Prangkio et al, 2012 ; Arbor et al, 2016 ; Serra-Batiste et al, 2016 ; Lee et al, 2017 ; Julien et al, 2018 ; Ciudad et al, 2020 ; Ruiz-Arias et al, 2020 ; Venko et al, 2021 ).…”
Section: Amyloid β Toxicity Related To Membrane Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyloid β peptides have been shown to oligomerize into ion-permeable transmembrane pores of varying structure, composition, and permeability. Aβ42 oligomers are known to adopt a β-sheet-rich structure in the presence of membrane lipids and self-organize into transmembrane channels permeable to calcium ions, which can cause cell death (Prangkio et al, 2012 ; Arbor et al, 2016 ; Serra-Batiste et al, 2016 ; Lee et al, 2017 ; Julien et al, 2018 ; Ciudad et al, 2020 ; Ruiz-Arias et al, 2020 ; Venko et al, 2021 ).…”
Section: Amyloid β Toxicity Related To Membrane Cholesterolmentioning
confidence: 99%
“…The Aβ-membrane interaction begins with the formation of electrostatic interactions of the basic amyloid residues with the negative charge of sialic acid on gangliosides, whereupon the peptide inserts into the hydrophobic zone of the bilayer with the help of cholesterol molecules. Then, Ca 2+ -permeable pore formation may occur (Lin et al, 2008 ; Di Scala et al, 2016 ; Venko et al, 2021 ). In another study, Aβ monomers bound to raft-like dipalmitoyl-PC:Chol:GM1 membranes and were incorporated into the bilayer only when both GM1 and cholesterol were present.…”
Section: The Involvement Of Other Lipidsmentioning
confidence: 99%
“…Another important and less-understood aspect of lipid interaction is the depth of insertion of the oligomers into the lipid bilayers. In this context, we note that one suggested mechanism of amyloid toxicity is the formation of unregulated ion channels in the membrane, ,,, and the process of the formation of ion channels was found to be dependent on local membrane organization . Such channel formation would require insertion of the oligomers into the membrane.…”
Section: Discussionmentioning
confidence: 88%
“…Exposure to oligomeric Aβ was shown to cause an increase in calcium flow across the membrane [ 120 ] inhibited by submillimolar concentrations of Zn 2+ and Cu 2+ ions [ 121 ]. According to some reports, the channel-like structures formed by Aβ oligomers [ 122 , 123 , 124 ] can influence the electrical potential of the neurons [ 125 ], and short-term memory impairments induced by Aβ oligomers can be caused by an increase in the local concentration of Zn 2+ in the presynaptic region [ 126 ]. Electrophysiological measurements revealed that Aβ 1–42 peptides can form at least three different types of ion channels differing in permeability, whereas Aβ 1–40 peptides form no ion channels [ 127 ].…”
Section: Structural Properties Of Aβ Monomers and Aggregatesmentioning
confidence: 99%